the ways I’ve been feeding it - Haines, Rayanne (My University, 2024)
this past summer, a little high, i plunged into the pacific. shoved an empty bottle of lager, all that was left in the fridge, under my beach bag so, i wouldn’t forget it
Keywords: poetry; CanLit; creative work